CAPIM-COLONIÃO E SEUS EFEITOS SOBRE O CRESCIMENTO INICIAL DE CLONES DE Eucalyptus × urograndis - Cruz, Michelle Barbeiro Da; Alves, Pedro Luís Da Costa Aguiar [UNESP]; Karam, Décio; Ferraudo, Antônio Sérgio [UNESP] (Universidade Federal de Santa Maria, 2010)
This study aimed to evaluate the guinea grass effect (Panicum maximum) on the initial growth of different Eucalyptus × urograndis clones. Two assays were established with eucalyptus clones and guinea grass seedlings. The plants were grown in plots with cement borders filled with soil. Each plot received a eucalyptus seedling. The first assay had a completely randomized experimental design, with three replications, and treatments in a 5x2 factorial scheme (five eucalyptus clones and the absence or presence of two guinea grass plants at 10 cm distance from eucalyptus seedling). The second assay was similar to the first, however with three eucalyptus clones. The experimental design was completely randomized, with five replications, and a 3x2 factorial scheme (three eucalyptus clones and the absence or presence of two guinea grass plants). The presence of eucalyptus clones did not affect guinea grass development. The eucalyptus clones that coexisted with guinea grass plants did not show differences in their development, making the clones equal when under competition. The most susceptible characteristics of eucalyptus clones to guinea grass were foliar area, shoot and stem dry matter. Clone 3 showed the most sensitivity to guinea grass, and clone 1 was the most tolerant, but all clones studied suffered a negative interference from guinea grass.

Esta pesquisa teve o objetivo de avaliar o efeito da convivência de capim-colonião sobre o crescimento inicial de plantas de clones de eucalipto. Foram instalados dois ensaios com mudas de clones de eucalipto e de capim-colonião, que cresceram em parcelas delimitadas lateralmente por paredes de alvenaria preenchidas com terra. O primeiro ensaio obedeceu ao delineamento experimental inteiramente casualizado, com três repetições, e tratamentos em esquema fatorial 5 x 2 (cinco clones de eucalipto, e a ausência ou presença de duas plantas de capim-colonião plantadas a 10 cm da muda de eucalipto). O segundo ensaio foi semelhante ao primeiro, porém, com apenas três clones de eucalipto, cinco repetições, e tratamentos em esquema fatorial 3 x 2 (três clones de eucalipto e a ausência ou presença de capim-colonião). Os clones de eucalipto não afetaram de modo diferenciado o crescimento de capim-colonião, sendo que aqueles que conviveram com a planta daninha não apresentaram diferença no seu desenvolvimento, igualando-os quando sob competição. As características dos clones de eucalipto mais sensíveis à convivência com capim-colonião foram: área foliar, matéria seca de folhas e caule. O clone 3 foi o que se mostrou mais sensível à convivência com capim-colonião e o clone 1 mais tolerante, porém todos os clones estudados tiveram influência negativa da convivência com capim-colonião.
GUINEA GRASS AND ITS EFFECTS ON THE INITIAL GROWTH OF Eucalyptus × urograndis CLONES
Keywords: Panicum maximum; competition; Eucalyptus × urograndis; interference; Panicum maximum; competição; Eucalyptus × urograndis; interferência